A Comprehensive Review of The Complex Causes of Fluorosis - Abeer shams; Ali Kareem; Heba mahgoob; Khalid Zainualbdeen (Baghdad Journal of Biochemistry and Applied Biological Sciences, 2025)
Many reviews and studies have brought to light the varied nature of the causes of fluorosis, as well as the necessity of conducting an in-depth investigation to guide strategies for prevention and management. Overconsumption of fluoride over an extended period, particularly when teeth or bones are growing, causes fluorosis, whether it affects the bones or teeth. The amount, timing, and duration of fluoride treatment all influence how serious the illness is. Dental fluorosis rarely manifests in its more severe forms; most cases are extremely moderate to mild. It has also been investigated how fluoride affects the immune system, the intestinal mechanical barrier, and innate immunity. In addition, current research has concentrated on the global impacts of skeletal fluorosis and the role oxidative stress plays in its advancement. The reviews emphasize how important prevention is and draw attention to the lack of specific treatments for skeletal fluorosis. The comprehensive results of the study underscore the intricacy of fluorosis and the necessity for comprehensive approaches to prevention and treatment.